Learning Quality Management Junior High School Accredited "A " (Multi-Site Study At Eben Haezar 1 Christian , Don Bosco Frater And SMP NEGERI 6 SMP In Manado City) - Sumenda, Lusia; Lumapow, Harol; Sumual, Tinneke; Lengkong, Jeffry (International Journal of Information Technology and Education, 2024)
Quality management of learning in schools greatly affects student learning activities. The quality of school graduates is a reflection of a quality in the school. This study aims to obtain the results of descriptive analysis of a situation from three accredited schools in Manado City, namely Eben Haezar 1 Christian Middle School, Manado, Bosco Manado Brother Middle School and Manado 6 Public Middle School. This study uses a qualitative approach with the survey/ observation method. The population of this study was the Principal and several teachers from three accredited junior high schools (Eben Haezar 1 Christian Middle School, Don Bosco Middle School and Manado 6 Public Middle School) in Manado City, North Sulawesi Province. The sample method used is a random sample. The research data was collected by observation, interviews and documentation and then analyzed by a single analysis and cross -site analysis. Conclusion Based on the results of this study is the application of management functions (planning, organizing, implementing, supervising) in Eben Haezar 1 Christian Middle School, Don Bosco Brother Middle School and SMP Negeri 6 in Manado City.